PEMBUATAN VCO (Virgin Coconut Oil) DARI KELAPA HIJAU DAN KELAPA HIBRIDA DENGAN METODE DINGIN - Gusti A.R Thamrin (Jurnal Hutan Tropis, 2011)
The purpose of this study was to determine the manufacture of VCO (Virgin Coconut Oil) by the method of cold, and knowing the number of VCO is in a green coconut and coconut hybrids. The results of this study can provide benefits and helpful information for producers of coconut, in particular, and for all of us in general, because it is rich in coconut in South Kalimantan.         The results of the VCO heavy green coconut on each treatment is 1.1 = 85 ml, 1.2 ml = 87 A, and A 1.3 = 87 ml, with an average value of 85.6 ml. As for the coconut hybrid VCO = 0. Can be made into a green coconut because the VCO has a fairly large fruit, meat is not so thick and less fruit than the hybrid coconut. While the hybrid coconut oil can not be used as a VCO may be due to age berbuahnya hybrid coconuts faster and more and form a smaller but has a thickness of the meat is thicker than the green coconut meat. The process of making coconut hybrids use the same method with cold green coconut, but at the time of the separation process that consists of oil, blendo and water for 24 hours, coconut hybrids only form 2 layers in the upper layer blendo lightly browned and remove unpleasant odors and bottom layer of water in there.Keywords : Virgin Coconut Oil, Green Coconut, Hybrid coconut